ENVIRONMENTAL IMPACT OF THE TEXTILE INDUSTRY AND THEIR MITIGATION SOLUTIONS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article analyzes the negative impact of the textile industry on theenvironment, including water and air pollution, soil degradation, and the problem ofsolid waste. It also presents proposals and solutions for establishing environmentallysustainable production.